Economic Geographical Features Of The Development Of The Oil And Gas Industry Of Kashkadarya Region - Olimova D.A. (Zien Journals, 2025)
This article analyzes the role of the oil and gas industry in the economy of the Kashkadarya region and its economic and geographical features. The region is one of the largest fuel and energy bases of Uzbekistan, where the Mubarak gas processing plant, the Shurtan gas and chemical complex and other important industrial enterprises operate. During the study, factors affecting the territorial development of the oil and gas industry, production infrastructure and the contribution of this industry to the socio-economic development of the region were analyzed. The environmental consequences of oil and gas production and processing processes were also considered
Keywords: Kashkadarya region; oil and gas industry; economic geographical position